Strategic Communication Laboratory for Employment. Analysis of 16 years of Experiences from the Employment Service of the University of Alicante - Torres Valdés, Rosa María (Estudios sobre el Mensaje Periodístico, 2013)
This work covers the period 19942010, and shows an analysis of communication research on university employment. It starts with exploratory studies about the state of the art both in theory and in business and media, with the purpose of obtaining useful information in order to designing communication strategies, implement them, evaluate impact and act accordingly with the results. Situation, circumstances, stake holders involved and variable of influence were (and remain) so, a research action approach that was a need. This article reflects the effort to consider the communication as a strategic element for the carrier office of the university (GIPE) which could be considered a case of study.